Insights into the stability of retained austenite during wear - Neoga, Suruj Protim; Lodh, Arijit; Karmakar, Anish; Nair, Akhil G.; Dasgupta, Arup; Bakshi, Subhankar Das; Das, Sourav (Taylor and Francis, 2022)
Transformation-induced plasticity mechanism is a very interesting phenomenon wherein a certain amount of austenite, which is thermally stable at room temperature but can be transformed to martensite during deformation, is retained in the microstructure. The amount of deformation (either by tensile, compressive or shear) that the austenite regions can withstand before they transform to martensite depends on their stability which is a function of the chemical-free energy and the severity of straining. In the current work, a bainitic steel with some retained austenite (RA), exposed to sliding wear in a pin-on-disc wear testing machine, was considered for the study. This paper aims to quantify the shear strain developed in the deformed subsurface region due to wear by using a simple image digitisation technique, and the stability aspect of RA for a complicated deformation mechanism like wear was studied considering the thermodynamics of austenite to ferrite transformations.
Keywords: Wear; subsurface deformation; carbide-free bainite; deformation induced martensitic transformation; model development